Studi Takhrij dan Syarah Hadis : Esensi Wudhu dalam Hadis Riwayat Muslim No. 360 - sadiah, nila (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2023)
Discussing the hadith about ablution is the purpose of this study. The author chose to use a qualitative approach by applying the descriptive-analytical method for this research. This study shows the results that the hadith discussed is of saheeh quality, and it can be concluded that the Hadith narrated by Muslim no. 360 is good to be used as a motivation in perfecting ablution.